The Impact of Economic Policy Reforms on Labour and the Nigerian Civil Society: A Stakeholders’ Dialectics - Fajana, Sola (Archives of Business Research, 2019)
The objective of this paper is to examine the impact of current reforms on labour and the civil society in Nigeria. The targeted outcome of the reforms essentially is to reduce poverty and generally improve the lot of the people. It is therefore significant to examine the extent to which the reforms are affecting, positively or negatively, the Nigerian people. This paper therefore provides an overview of the extent to which stakeholders in the Nigerian project are variously affected by current economic reforms, their reactions and the ways in which future policy reforms should be approached. The paper relies on reviews of archival materials and focal interviews of relevant groups to provide insightful information. It was found that reactions have been largely impulsive, lacking coherent future follow-through actions to consolidate initial gains. It is now learnt from lessons of experience that reforms must be appropriate, timely but not impulsive, and well-articulated to achieve the targeted results. It is recommended that policy reforms should be jointly initiated, considered and driven by all constituents to the Nigerian project, to achieve a sense of ownership and high volume commitment.